A new Tropocyclops (Copepoda, Cyclopidae) from Lake Matano, Indonesia - Defaye, Danielle (Zootaxa, 2007)
A new species of Tropocyclops, from the subfamily Eucyclopinae (Cyclopoida, Cyclopidae) is described on the basis of specimens recently collected from the deep waters of the ancient Lake Matano, Indonesia. Tropocyclops matanoensis n. sp., is distinguished from other species in the genus by the armature of P5 (with one seta and one spine) and the absence of lateral hairs on the somite bearing it, the antenna with only one seta on the antero-distal corner, the special shape of the seminal receptacle in female, and several other characters detailed in this study. A discussion of the genus Tropocyclops and the morphological characteristics of its representatives is given.